Alliance between the right to identity and the right to family life as a constitutional/conventional basis to rethink adoption in a contemporary key - Marisa Herrera (Oñati Socio-Legal Series)
In this essay we propose to rethink the centrality of the right to identity as the base human right or backbone of the adoptive legal system in Argentine law. It happens that the right to identity, although always in a relational context such as that contained in filiation, focuses on the satisfaction and protection of people as such, would encounter certain limitations when delving into all interactions – beyond the binarism. relational – that involve certain contemporary problems of adoption. For the purposes of this interpellative task, we are encouraged to get into the ring and thus dispute this centrality in light of the development of the right to family life, taking arts as a starting point. 17 of the ACHR and 8 of the ECHR with the consequent dynamic interpretation carried out by the Inter-American Court of Human Rights and the European Court of Human Rights.